Enhancing the long-term abstinence rate of smoking through telemedicine: A multicenter, retrospective cohort study in Japan - Kazuki Takakura; Tetsuro Ishizawa; Yoshihiko Aoki; Kei Matsumoto; Toshikazu D. Tanaka; Muneyuki Koyama; Yuji Kinoshita; Saburo Ito; Kazuhiro Yoshiuchi; Machi Suka (PLoS ONE, 2026)
The aim of this study is to analyze the differences between telemedicine and face-to-face examinations for smoking cessation in terms of long-term abstinence and completion rates in a large Japanese population. Although the effectiveness of various smoking cessation methods has been confirmed, the treatment outcomes of face-to-face interviews for tobacco cessation are still insufficient, because it is bother to go to a clinic regularly for most patients. In line with current trends of developing digital healthcare services, we assessed the role of telemedicine as a potential tool in smoking cessation clinics. A total of 5005 current smokers who applied for the telemedicine smoking cessation program between April 2021 and December 2022 and a total of 1308 current smokers who visited some smoking cessation clinics between April 2016 and March 2017 were included. Clinical data, such as age, sex, Brinkman index, were collected from all the participants, in addition to a preliminary questionnaire including smoking habits, reason for applying and self-efficacy for smoking cessation. This online program consists of four sessions in the first 8 weeks, with a 1-year follow-up period (final follow-up at 52 weeks). The success rates of long-term smoking abstinence at week 52 and the completion rates of scheduled treatment with varenicline or nicotine patches were compared between the telemedicine and face-to-face examinations. Data on face-to-face examinations were obtained from the database of the Ministry of Health, Labor and Welfare in Japan for comparison. A total of 3708 patients (3364 men and 352 women) were analyzed. The completion rate of this program (68.2%) was significantly greater than that of face-to-face examinations (29.8%). The long-term abstinence rate was significantly greater with telemedicine than with conventional examination (P < 0.005). In conclusion, the findings revealed that telemedicine is helpful for long-term abstinence from smoking on the basis of improved availability and accessibility.